Understanding the ASEAN economic community: pragmatism versus conceptualism. Issue 5 (20th October 2019) - Pelkmans, Jacques
ABSTRACT: The ASEAN Economic Community, born in 2003 and developed over the next 12 years, aims to build a 'single market' whilst 'enhancing the production base' in ASEAN for global and regional value-chains. The paper attempts to understand the AEC via a conceptual as well as a pragmatic approach. It summarizes achievements up to 2015 and assesses the 2025 Blueprint in some detail. At times the latter reads like a Roadmap full of details but measures often remain open-ended or somewhat vague, a typical ASEAN characteristic. What ultimately matters to ASEAN is economic growth and the AEC may well serve as a handmaiden to sustained high growth.